Ester-based semi-synthetic cutting fluid and preparation method thereof

Through the design of the ester-based semi-synthetic cutting fluid, the combination of ester base oil, environmentally friendly emulsifier, nanoadditive and self-repair lubricant is used to solve the problem of difficult temperature and friction control in titanium alloy processing, and the effect of efficient lubrication, low carbon emissions and long-life tools is achieved.

CN119144381BActive Publication Date: 2025-04-18NANTONG KEXING CHEM
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411409502.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-04-18
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

Traditional cutting fluids are difficult to effectively reduce processing temperature and friction in titanium alloy processing, resulting in increased tool wear, low processing efficiency, and carbon emission problems.

Method used

The dispersion of nanoparticles and the stability of cutting fluid are optimized by combining ester base oil, environmentally friendly emulsifiers, nanoadditives and self-healing lubricants, and the dispersion of nanoparticles and the stability of cutting fluid are reduced, thereby reducing hydrolysis and oxidation reactions.

Benefits of technology

It significantly improves the lubricating performance and thermal stability of the cutting fluid, extends the tool life, reduces carbon emissions, and improves processing efficiency and quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005314656970000061
    Figure GDA0005314656970000061
  • Figure GDA0005314656970000111
    Figure GDA0005314656970000111
Patent Text Reader

Abstract

The present invention relates to the technical field of metal cutting fluids, and in particular to an ester-based semi-synthetic cutting fluid and a preparation method thereof, which comprises, by weight, 50-70 parts of ester base oil; 10-20 parts of environmentally friendly emulsifiers; 5-10 parts of nano additives; 5-10 parts of self-repairing lubricants; 1-5 parts of low-carbon additives; 0.5-1 parts of polyvinyl alcohol; the self-repairing lubricant is divided into reagent A and reagent B according to a ratio of 5-7:3-5, reagent A is mixed with nano additives, polyvinyl alcohol is added to form a suspension, and then added to the reaction system; reagent B is used to be directly added to the reaction system. It is intended to optimize the dispersibility of nanoparticles while maintaining the overall stability and performance of the cutting fluid. While pursuing efficient lubrication, rust prevention and cleaning performance, the cutting fluid is committed to reducing carbon emissions in the cutting process and promoting green manufacturing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal cutting fluids, and in particular to an ester-based semi-synthetic cutting fluid and a preparation method thereof. Background Art

[0002] Titanium alloys are widely used in high-end manufacturing fields such as aerospace due to their excellent performance. However, due to the difficulty of processing, the processing cost remains high, which limits the use of titanium alloys in a wider range of industries. The reason is that, first of all, the thermal conductivity of titanium alloys is low, and the heat generated during the processing is difficult to conduct effectively. Especially during cutting, the contact area between the tool and the chip is small, the friction coefficient is large, and the heat in the cutting area is concentrated in a small area near the blade, which cannot be diffused to the chip or workpiece in time, resulting in a rapid increase in local temperature.

[0003] In addition, titanium alloys have strong chemical activity in high temperature environments and are prone to react with oxygen, nitrogen and other elements in the air to produce hard compounds such as titanium nitride and titanium oxide. This reaction causes work hardening on the surface of the workpiece, which increases the surface hardness of the titanium alloy, while reducing the plasticity of the material and weakening its fatigue resistance. The dual effects of high temperature and work hardening intensify tool wear, further increasing the difficulty and cost of processing.

[0004] Therefore, in the cutting of titanium alloys, the formulation and process design of cutting fluid are particularly critical. The cutting fluid not only needs to have a good cooling effect to quickly reduce the temperature of the cutting zone, but also has excellent lubrication properties to reduce the friction between the tool and the workpiece, so as to extend the tool life, improve processing efficiency and workpiece quality.

[0005] Although traditional mineral oil cutting fluids perform well in some low-demand processing, their lubrication and cooling performance is insufficient in the processing of high-strength materials (such as titanium alloys). Due to the poor thermal stability of mineral oil, it is easy to deteriorate in high temperature environments, resulting in failure of the lubricating film, which in turn increases tool wear. Especially when processing titanium alloys, traditional cutting fluids are difficult to effectively reduce the processing temperature, resulting in increased tool wear, low processing efficiency, and difficulty in ensuring quality. In addition, traditional cutting fluids often generate a large amount of carbon emissions during production, use, and disposal.

[0006] Compared with other chemical synthetic base oils (such as poly-α-olefin (PAO), silicone oil and mineral oil, etc.), ester base oils have excellent lubrication performance, excellent thermal stability, environmental protection and biodegradability, and excellent cooling performance. These advantages make ester base oils an ideal choice for high-performance, environmentally friendly cutting fluids, especially for high-demand titanium alloy cutting applications. However, the application of ester base oils also faces the following challenges:

[0007] (1) Ester base oils are prone to hydrolysis in humid environments or in water-containing cutting fluid formulations. The hydrolysis process causes the ester bonds to break, generating fatty acids and alcohols. These generated fatty acids will reduce the lubricity of the cutting fluid and may increase the acidity of the cutting fluid, corrode the processing equipment and workpiece surface, and affect the processing quality. In addition, the hydrolysis reaction will accelerate the deterioration of the cutting fluid, shorten its service life, and increase maintenance costs.

[0008] (2) Ester base oils are prone to oxidation reactions in high temperature and air contact environments to generate peroxides. These peroxides not only reduce the lubrication performance of the cutting fluid, but may also trigger secondary chemical reactions, further generating byproducts that are harmful to the cutting fluid, resulting in a decrease in the performance of the cutting fluid. Especially in the high-temperature cutting environment of titanium alloys, the oxidation reaction is more significant, accelerating the degradation of the cutting fluid, causing it to lose its lubrication function, resulting in an increase in the friction coefficient during the processing process and increased tool wear.

[0009] Therefore, it is particularly important to develop a cutting fluid that has both excellent performance and meets environmental protection requirements.

[0010] The information disclosed in this background technology section is only intended to deepen the understanding of the overall background technology of the present invention, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art known to those skilled in the art. Summary of the invention

[0011] The first object of the present invention is to provide an ester-based semi-synthetic cutting fluid, in which the self-healing lubricant is divided into two parts after preparation, one part of which is used to mix with nano additives and add polyvinyl alcohol, while the other part is directly added to the cutting fluid, aiming to optimize the dispersion of nanoparticles while maintaining the overall stability and performance of the cutting fluid.

[0012] The above technical objectives of the present invention are achieved through the following technical solutions:

[0013] An ester-based semi-synthetic cutting fluid, comprising, by weight, 50-70 parts of ester base oil; 10-20 parts of environmentally friendly emulsifier; 5-10 parts of nano additives; 5-10 parts of self-repairing lubricants; 1-5 parts of low-carbon additives; and 0.5-1 part of polyvinyl alcohol.

[0014] The present invention adopts ester base oil as the main component to prepare cutting fluid. The use of environmentally friendly emulsifier can isolate the water phase and the oil phase to a certain extent, reduce the risk of hydrolysis of the ester base oil, enhance the water repellency of the cutting fluid, and reduce the occurrence of hydrolysis reaction. On this basis, the self-repairing lubricant prepared from vegetable oil composite phosphate can further inhibit hydrolysis and have certain antioxidant properties. The phosphate group has good lipophilicity and can form a stable protective layer in the oil phase. This protective layer can effectively isolate moisture and slow down the contact between moisture and ester group, thereby inhibiting the hydrolysis reaction of ester base oil. In addition, the vegetable oil itself has good biodegradability and low hydrolysis tendency, and forms a synergistic effect with the ester base oil to further reduce the risk of hydrolysis. When it is used for titanium alloy cutting, the phosphate group can form a protective film on the metal surface, which can prevent direct contact between oxygen and metal in a high temperature environment and slow down the occurrence of oxidation reaction.

[0015] The self-repairing lubricant is divided into reagent A and reagent B in a ratio of 5-7:3-5. Reagent A is mixed with nano additives and then added with polyvinyl alcohol to form a suspension, which is then added to the reaction system; reagent B is used to be directly added to the reaction system.

[0016] Specifically, the molecular weight of polyvinyl alcohol is 5000 to 20000, and the alcoholysis degree of polyvinyl alcohol is about 80%, which prevents close contact and agglomeration between nanoparticles, thereby improving dispersibility. Polyvinyl alcohol is concentrated in part A mixed with nano-additives, which can ensure efficient dispersion of nanoparticles in the self-healing lubricant and reduce the risk of agglomeration. It can also improve the viscosity of part A and the formation of a lubricating film, which helps to reduce friction and wear during the cutting process. Part B provides basic lubrication and stability of the cutting fluid, ensuring that good lubrication performance can be maintained under high shear and high temperature conditions. Since part B does not contain polyvinyl alcohol, it can prevent the viscosity of the entire cutting fluid system from being too high, and maintain good fluidity and cooling effects.

[0017] Preferably, the self-repairing lubricant is a composite phosphate of vegetable oil, and the mass ratio of phosphate to vegetable oil is 3-6:5-10; during the cutting process, the self-repairing lubricant can automatically re-adsorb and reorganize on the metal surface to repair the damaged lubricating layer. The present invention selects vegetable oil and phosphate with high thermal stability to prepare the self-repairing lubricant. Since vegetable oil is usually an esterification product of polyols, phosphate can be connected with the hydroxyl group on the vegetable oil. When the lubricating layer on the metal surface is damaged, the unreacted molecules can migrate to the damaged area, quickly cover and repair the worn parts, and play a self-repairing role. This dynamic adsorption process helps to maintain the integrity of the lubricating layer. During the processing and cutting of titanium alloys, the composite phosphate of vegetable oil can maintain its chemical and physical stability, is not easy to decompose or volatilize, and ensures that the lubricating film is still effective at high temperatures; vegetable oil-based phosphate has a certain antioxidant property, which can slow down the oxidation reaction of the metal surface under high temperature conditions and protect the workpiece and cutting tools from the influence of high temperature oxidation.

[0018] Preferably, the present invention determines the adsorption rate of the self-repairing lubricant under different conditions (temperature, shear rate, pressure, etc.) through friction and wear tests, and optimizes the ratio of phosphate ester to vegetable oil. The experiment includes the following experimental variables:

[0019] Temperature: Set a variety of temperature conditions (such as room temperature 25℃, 100℃, 150℃, 200℃) to simulate the temperature environment in different cutting processes.

[0020] Shear rate: Different shear rates (such as 500rpm, 1000rpm, 1500rpm) represent different cutting speeds.

[0021] Pressure: Set different pressure levels (such as 10N, 20N, 30N) to simulate different processing pressure environments.

[0022] Phosphate ester to vegetable oil ratio: For the self-healing lubricant, different mass ratios of phosphate ester to vegetable oil (such as 2:1, 3:2, 1:1, 2:3, 1:2) were set and experimental comparisons were conducted.

[0023] The specific experimental steps include the following:

[0024] (1) Prepare self-healing lubricant samples with different ratios of phosphate ester to vegetable oil and apply them on the surface of titanium alloy;

[0025] (2) On the tribometer, a spherical probe is placed in contact with a metal sample coated with a lubricant. Under different experimental conditions (temperature, shear rate, pressure), friction is applied and the change in friction force over time is recorded. The increase in friction force represents the damage of the lubricating film. When the friction force returns to a lower level, it indicates that the self-healing lubricant is re-adsorbed and a new lubricating film is formed;

[0026] (3) Repeat the experiment: Repeat each experimental condition multiple times to ensure the reliability and stability of the data;

[0027] The peak value of the friction coefficient after the lubricating film is damaged and the time to recover to the steady-state friction coefficient are recorded to represent the adsorption and repair rate of the lubricant. It can be seen that when the mass ratio of phosphate ester: vegetable oil is 3-4:6-7, a higher vegetable oil content can be provided, thereby ensuring the self-repair ability of the lubricating film. At the same time, due to the moderate content of phosphate ester, a stable protective layer can be formed on the metal surface, and it has good wear resistance and lubricity. It is suitable for scenes with high processing temperature and high lubrication and wear resistance, such as difficult-to-process materials such as titanium alloys.

[0028] Preferably, the vegetable oil is one or more of coconut oil and rapeseed oil, and the phosphate ester is triethyl phosphate or diethyl phosphate.

[0029] Preferably, the ester base oil includes one or more of neopentyl glycol dioleate, triethylene glycol dioleate, pentaerythritol oleate, pentaerythritol tetraisooctanoate, and dipentaerythritol oleate. The ester base oil has good thermal stability under high temperature conditions, avoids decomposition or generation of harmful substances during the cutting process, thereby maintaining the cooling effect. The preferred ester base oil is neopentyl glycol dioleate, which has high thermal conductivity to provide sufficient heat capacity to absorb the heat generated during the cutting process.

[0030] Preferably, the environmentally friendly emulsifier includes environmentally friendly sodium petroleum sulfonate and fatty alcohol ether emulsifier, and the environmentally friendly sodium petroleum sulfonate and fatty alcohol ether emulsifier are mixed in a mass ratio of 3:1.

[0031] Preferably, the nano additive is nano zinc titanate modified by a titanate coupling agent, and the particle size of the nano zinc titanate modified by a titanate coupling agent is in the range of 10 to 50 nm.

[0032] Zinc titanate has higher hardness and can provide stronger wear resistance when cutting high-strength materials such as titanium alloys. Zinc titanate has high-temperature stability, which makes it perform well under high-temperature cutting conditions and reduces the degradation of additives at high temperatures. However, zinc titanate has a high density, which makes it easy to settle in liquids, increasing the difficulty of dispersion. Titanate coupling agents form strong covalent bonds with the surface of zinc titanate through titanate groups. It can effectively improve the surface activity and dispersibility of particles, thereby enhancing their stability in the system.

[0033] Preferably, the nano additive is prepared by the following steps:

[0034] S11: Add nano zinc titanate to ethanol solvent, perform ultrasonic vibration to make it uniform, slowly add bis(dioctyloxy) dipropyl titanate, and keep stirring to ensure uniform mixing;

[0035] S12: Use ultrasonic oscillation and mechanical stirring to make bis(dioctyloxy)dipropyl titanate adhere to the surface of zinc titanate, coat the surface of nano zinc titanate, and form a lubricating film; ultrasonic dispersion technology can effectively destroy the agglomeration of nanoparticles, evenly distribute the particles in the liquid, reduce the adhesion between particles, break up the agglomerated particles, and effectively improve the dispersion effect.

[0036] S13: After the reaction is completed, the unreacted bis(dioctyloxy)dipropyl titanate and impurities are removed by centrifugation or filtration, and the washed product is dried in a vacuum environment at 60-80° C. to remove the residual solvent, thereby obtaining a surface-modified nano-additive.

[0037] Preferably, the low-carbon additive includes one or more of metal corrosion inhibitors, bactericides, and antioxidants. The metal corrosion inhibitors and antioxidants in the low-carbon additives can inhibit the corrosion of the metal surface, wherein the antioxidant can capture free radicals to prevent the chain oxidation reaction caused by them; the metal corrosion inhibitor forms a passivation layer on the metal surface to reduce the corrosion of the acidic substances generated by hydrolysis to the metal. By adding low-carbon additives, the cutting fluid can maintain chemical stability in a high temperature environment, reduce the performance degradation of the cutting fluid due to oxidation or corrosion, and extend its service life.

[0038] The second object of the present invention is to provide a method for preparing an ester-based semi-synthetic cutting fluid. The prepared cutting fluid, while pursuing high-efficiency lubrication, rust prevention and cleaning performance, is committed to reducing carbon emissions in the cutting process and promoting green manufacturing.

[0039] The above technical objectives of the present invention are achieved through the following technical solutions:

[0040] A method for preparing an ester-based semi-synthetic cutting fluid comprises the following steps:

[0041] S21: Heat the ester base oil to 60-70°C; maintain constant temperature for 30 minutes to ensure complete heating of the base oil and removal of impurities.

[0042] S22: Gradually add environmentally friendly emulsifier to the heated base oil, mix while stirring to ensure that the emulsifier is fully and evenly dispersed in the oil phase, and maintain a medium stirring speed to form a stable emulsified system; the stirring speed is controlled at 800-1200rpm, and stirring is continued for 20 minutes to form a stable emulsified system.

[0043] S23: Mix the vegetable oil and the phosphate ester uniformly according to the mass ratio to ensure that the two are fully mixed, and then separate them into reagent A and reagent B for later use;

[0044] S24: The nano-additives are gradually added to the reagent A and initially dispersed by high shear stirring or ultrasonic treatment to ensure that the nano-particles are distributed as evenly as possible in the liquid and reduce the possibility of initial agglomeration; then after the nano-particles are initially dispersed, polyvinyl alcohol is slowly added and stirred for 30 minutes to provide additional dispersion through polyvinyl alcohol to effectively prevent the re-agglomeration of particles, and then the obtained suspension is slowly added to the heated emulsification system and stirred continuously to ensure that the nano-additives are evenly dispersed; at this time, part A has both surface modification of zinc titanate and addition of polyvinyl alcohol, which provides stronger dispersion and stabilization capabilities. Double stability is achieved.

[0045] Polyvinyl alcohol has good solubility and hydrophilicity in the aqueous phase, which helps it to be evenly distributed in the emulsified system and enhances the dispersion effect of nanoparticles in the aqueous phase.

[0046] S25: adding reagent B to the emulsified system mixed in step S24, and continuing to stir to ensure uniformity;

[0047] S26: Add low-carbon additives as needed and stir to mix evenly, and obtain an ester-based semi-synthetic cutting fluid after cooling.

[0048] Preferably, in step S26, low-speed stirring is maintained during the cooling process to prevent stratification or precipitation.

[0049] In summary, the present invention has the following beneficial effects:

[0050] (1) The present invention uses ester base oil and environmentally friendly emulsifiers to produce a cutting fluid with good biodegradability, reducing the pollution of mineral oil and chemical additives in traditional cutting fluids. At the same time, the low-carbon additives in the cutting fluid can effectively reduce carbon emissions during the cutting process. On this basis, the present invention uses vegetable oil composite phosphate ester as a self-repairing lubricant, which can automatically adsorb to the metal surface during the cutting process to form a strong lubricating film. When the lubricating film is partially damaged, the phosphate group can be re-adsorbed, quickly repairing the worn parts and maintaining the integrity of the lubricating layer. This self-repairing function can effectively improve the lubrication effect during the cutting process, extend the tool life, and reduce downtime and maintenance costs under high temperature and high pressure processing environments.

[0051] (2) The vegetable oil composite phosphate and ester base oil in the present invention have excellent thermal stability, can maintain chemical and physical stability when cutting difficult-to-process materials such as titanium alloys, and are not easy to decompose or volatilize. This stability ensures that the lubricating film can still function in a high-temperature environment, reducing tool wear and improving processing quality. Due to the improved lubrication performance and self-repairing function, the cutting fluid can significantly reduce tool wear and passivation, and improve processing accuracy and efficiency. Especially in the processing of titanium alloys, the cutting fluid exhibits higher wear resistance, reduces downtime for maintenance, and reduces costs.

[0052] (3) The present invention reasonably controls the viscosity of the cutting fluid and separates some components of the self-repairing lubricant, thereby ensuring efficient lubrication and preventing the system from being too high in viscosity, thereby ensuring good fluidity and cooling effects. This allows lubrication to be maintained in a high shear environment without affecting its cooling and cleaning performance. By combining polyvinyl alcohol with a modified nano zinc titanate system, nanoparticles can form a stable dispersion system in the cutting fluid, reduce agglomeration, and thus enhance the anti-wear properties and lubrication effect of the cutting fluid. Nano additives have antioxidant properties and can effectively inhibit the oxidation reaction produced during high-temperature cutting, protect metal surfaces and cutting tools, and extend their service life. DETAILED DESCRIPTION

[0053] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined purpose of the invention, an ester-based semi-synthetic cutting fluid and a preparation method thereof proposed in accordance with the present invention, its specific implementation method, characteristics and effects are described in detail as follows.

[0054] Sources of raw materials used in the embodiments and comparative examples:

[0055]

[0056] Example 1

[0057] An ester-based semi-synthetic cutting fluid, comprising, by weight, 60 parts of ester base oil; 15 parts of environmentally friendly emulsifier; 8 parts of nano additives; 8 parts of self-repairing lubricant; 3 parts of low-carbon additives; and 0.8 parts of polyvinyl alcohol.

[0058] The self-healing lubricant is divided into reagent A and reagent B in a ratio of 7:3. Reagent A is mixed with nano additives and then added with polyvinyl alcohol to form a suspension, which is then added to the reaction system; reagent B is used to be directly added to the reaction system.

[0059] Among them, the self-repairing lubricant is a vegetable oil composite phosphate, and the mass ratio of phosphate to vegetable oil is 3:7; during the cutting process, the self-repairing lubricant can automatically re-adsorb and reorganize on the metal surface to repair the damaged lubricating layer. The vegetable oil is rapeseed oil, and the phosphate ester is triethyl phosphate. The low-carbon additives are 1 part each of benzotriazole (metal corrosion inhibitor), methylisothiazolinone (fungicide), and butylated hydroxytoluene (antioxidant). The ester base oil is neopentyl glycol dioleate. The environmentally friendly emulsifier is made by mixing environmentally friendly sodium petroleum sulfonate and fatty alcohol ether emulsifier in a mass ratio of 3:1.

[0060] The nano additive is nano zinc titanate modified by a titanate coupling agent, and the particle size of the modified nano zinc titanate ranges from 10 to 50 nm. The nano additive is prepared by the following steps:

[0061] S11: 5 g of nano zinc titanate was added to 100 mL of ethanol solvent, and ultrasonic vibration was performed to make it uniform. Then, 1 mL of bis(dioctyloxy) dipropyl titanate and 0.2 mL of deionized water were slowly added under stirring. The bis(dioctyloxy) dipropyl titanate was dissolved in ethanol and a lubricating coating layer was formed on the surface of zinc titanate. Stirring was continued at a speed of 800 rpm for 30 min to ensure that the bis(dioctyloxy) dipropyl titanate was uniformly mixed.

[0062] S12: The mixture after the reaction in S11 was heated to 50°C, and subjected to ultrasonic treatment at this temperature for 1 hour, while stirring at a speed of 1000 rpm. The bis(dioctyloxy)dipropyl titanate was uniformly coated on the surface of the nano zinc titanate to form a modified film, providing better dispersibility and stability. Ultrasonic treatment helps to break up the agglomeration of nanoparticles and ensure the uniform distribution of particles in the solution;

[0063] S13: After the reaction is completed, the mixture is centrifuged or filtered to remove unreacted reactants and impurities. It is then washed three times with ethanol or deionized water to ensure that there is no residue on the surface. Finally, the washed product is placed in a vacuum drying oven at 70°C for 12 hours to remove the residual ethanol solvent, and finally a surface-modified modified nano zinc titanate system is obtained.

[0064] A method for preparing an ester-based semi-synthetic cutting fluid comprises the following steps:

[0065] S21: Heat the ester base oil to 65°C; maintain the constant temperature for 30 minutes to ensure complete heating of the base oil and removal of impurities.

[0066] S22: Gradually add environmentally friendly emulsifier to the heated base oil, mix while stirring to ensure that the emulsifier is fully and evenly dispersed in the oil phase, and maintain a medium stirring speed to form a stable emulsified system; the stirring speed is controlled at 1000rpm, and stirring is continued for 20 minutes to form a stable emulsified system.

[0067] S23: Mix the vegetable oil and the phosphate ester uniformly according to the mass ratio to ensure that the two are fully mixed, and then separate them into reagent A and reagent B for later use;

[0068] S24: gradually adding the nano-additive to reagent A and preliminarily dispersing it by high shear stirring or ultrasonic treatment can ensure that the nano-particles are distributed in the liquid as evenly as possible and reduce the possibility of initial agglomeration; then after the nano-particles are preliminarily dispersed, slowly adding polyvinyl alcohol and continuing stirring for 30 minutes to effectively prevent the re-agglomeration of the particles, and then slowly adding the obtained suspension to the heated emulsification system and continuing stirring to ensure that the nano-additives are evenly dispersed;

[0069] S25: adding reagent B to the emulsified system mixed in step S24, and continuing to stir to ensure uniformity;

[0070] S26: Add low-carbon additives as needed and stir to mix evenly, keep stirring at a low speed to cool to prevent stratification or precipitation, and obtain an ester-based semi-synthetic cutting fluid after cooling.

[0071] Example 2

[0072] An ester-based semi-synthetic cutting fluid, comprising, by weight, 50 parts of ester base oil; 10 parts of environmentally friendly emulsifier; 5 parts of nano additives; 5 parts of self-repairing lubricant; 1 part of low-carbon additive; and 0.5 parts of polyvinyl alcohol.

[0073] The self-healing lubricant is divided into reagent A and reagent B in a ratio of 7:3. Reagent A is mixed with nano additives and then added with polyvinyl alcohol to form a suspension, which is then added to the reaction system; reagent B is used to be directly added to the reaction system.

[0074] Among them, the self-repairing lubricant is a vegetable oil composite phosphate ester, and the mass ratio of phosphate ester to vegetable oil is 4:6; the vegetable oil is a mixture of coconut oil and rapeseed oil in a ratio of 1:1, and the phosphate ester is diethyl phosphate. The low-carbon additives are 0.5 parts each of benzotriazole (metal corrosion inhibitor) and methylisothiazolinone (fungicide). The ester base oil is triethylene glycol dioleate. The environmentally friendly emulsifier is made by mixing environmentally friendly sodium petroleum sulfonate and fatty alcohol ether emulsifier in a mass ratio of 3:1.

[0075] The preparation method of the nano-additive and ester-based semi-synthetic cutting fluid is prepared by adopting the steps of Example 1.

[0076] Example 3

[0077] An ester-based semi-synthetic cutting fluid, comprising, by weight, 70 parts of ester base oil; 20 parts of environmentally friendly emulsifier; 10 parts of nano additive; 10 parts of self-repairing lubricant; 5 parts of low-carbon additive; and 1 part of polyvinyl alcohol.

[0078] The self-healing lubricant is divided into reagent A and reagent B in a ratio of 6:4. Reagent A is mixed with nano additives and then added with polyvinyl alcohol to form a suspension, which is then added to the reaction system; reagent B is used to be directly added to the reaction system.

[0079] Among them, the self-repairing lubricant is a vegetable oil composite phosphate, and the mass ratio of phosphate ester to vegetable oil is 4:6; the vegetable oil is coconut oil, and the phosphate ester is triethyl phosphate. The low-carbon additive is 2.5 parts of benzotriazole (metal corrosion inhibitor) and butylated hydroxytoluene (antioxidant). The ester base oil is pentaerythritol oleate. The environmentally friendly emulsifier is made by mixing environmentally friendly sodium petroleum sulfonate and fatty alcohol ether emulsifier in a mass ratio of 3:1.

[0080] The preparation method of the nano-additive and ester-based semi-synthetic cutting fluid is prepared by adopting the steps of Example 1.

[0081] Comparative Example 1

[0082] An ester-based semi-synthetic cutting fluid, comprising, by weight, 60 parts of ester base oil; 15 parts of environmentally friendly emulsifier; 8 parts of nano additives; 8 parts of self-repairing lubricant; and 3 parts of low-carbon additives;

[0083] Among them, the self-repairing lubricant is a vegetable oil composite phosphate, and the mass ratio of phosphate ester to vegetable oil is 3:7; the vegetable oil is rapeseed oil, and the phosphate ester is triethyl phosphate. The low-carbon additives are 1 part each of benzotriazole (metal corrosion inhibitor), methylisothiazolinone (fungicide), and butylated hydroxytoluene (antioxidant). The ester base oil is neopentyl glycol dioleate. The environmentally friendly emulsifier is prepared by mixing environmentally friendly sodium petroleum sulfonate and fatty alcohol ether emulsifier in a mass ratio of 3:1.

[0084] The preparation steps of the nano additive are the same as those in Example 1 and will not be repeated here:

[0085] A method for preparing an ester-based semi-synthetic cutting fluid comprises the following steps:

[0086] S21: Heat the ester base oil to 65°C; maintain the constant temperature for 30 minutes to ensure complete heating of the base oil and removal of impurities.

[0087] S22: Gradually add environmentally friendly emulsifier to the heated base oil, mix while stirring to ensure that the emulsifier is fully and evenly dispersed in the oil phase, and maintain a medium stirring speed to form a stable emulsified system; the stirring speed is controlled at 1000rpm, and stirring is continued for 20 minutes to form a stable emulsified system.

[0088] S23: gradually adding the nano-additives into the emulsified system and preliminarily dispersing them by high shear stirring or ultrasonic treatment;

[0089] S24: The vegetable oil and the phosphate ester are mixed uniformly according to the mass ratio to ensure that the two are fully mixed, and then added to the emulsified system mixed in step S23, and the mixing is continued to ensure uniformity;

[0090] S25: Add low-carbon additives as needed and stir to mix evenly, keep stirring at a low speed to cool to prevent stratification or precipitation, and obtain an ester-based semi-synthetic cutting fluid after cooling.

[0091] Comparative Example 2

[0092] An ester-based semi-synthetic cutting fluid, comprising, by weight, 60 parts of ester base oil; 15 parts of environmentally friendly emulsifier; 8 parts of nano additives; 8 parts of polyvinyl alcohol; and 3 parts of low-carbon additives;

[0093] Among them, the low-carbon additives are 1 part each of benzotriazole (metal corrosion inhibitor), methylisothiazolinone (fungicide), and butylated hydroxytoluene (antioxidant). The ester base oil is neopentyl glycol dioleate. The environmentally friendly emulsifier is prepared by mixing environmentally friendly sodium petroleum sulfonate and fatty alcohol ether emulsifier in a mass ratio of 3:1.

[0094] The preparation steps of the nano additive are the same as those in Example 1 and will not be repeated here:

[0095] A method for preparing an ester-based semi-synthetic cutting fluid comprises the following steps:

[0096] S21: Heat the ester base oil to 65°C; maintain the constant temperature for 30 minutes to ensure complete heating of the base oil and removal of impurities.

[0097] S22: Gradually add environmentally friendly emulsifier to the heated base oil, mix while stirring to ensure that the emulsifier is fully and evenly dispersed in the oil phase, and maintain a medium stirring speed to form a stable emulsified system; the stirring speed is controlled at 1000rpm, and stirring is continued for 20 minutes to form a stable emulsified system.

[0098] S24: gradually adding the nano-additives to the emulsified system and preliminarily dispersing them by high shear stirring or ultrasonic treatment can ensure that the nanoparticles are distributed as evenly as possible in the liquid and reduce the possibility of initial agglomeration; then after the nanoparticles are preliminarily dispersed, slowly adding polyvinyl alcohol and continuing stirring for 30 minutes to ensure uniformity;

[0099] S25: Add low-carbon additives as needed and stir to mix evenly, keep stirring at a low speed to cool to prevent stratification or precipitation, and obtain an ester-based semi-synthetic cutting fluid after cooling.

[0100] Comparative Example 3

[0101] An ester-based semi-synthetic cutting fluid, comprising, by weight, 60 parts of ester base oil; 15 parts of environmentally friendly emulsifier; 8 parts of nano zinc titanate; 8 parts of self-repairing lubricant; 3 parts of low-carbon additive; and 0.8 parts of polyvinyl alcohol.

[0102] The self-healing lubricant is divided into reagent A and reagent B in a ratio of 7:3. Reagent A is mixed with nano additives and then added with polyvinyl alcohol to form a suspension, which is then added to the reaction system; reagent B is used to be directly added to the reaction system.

[0103] Among them, the self-repairing lubricant is a vegetable oil composite phosphate, and the mass ratio of phosphate ester to vegetable oil is 3:7; the vegetable oil is rapeseed oil, and the phosphate ester is triethyl phosphate. The low-carbon additives are 1 part each of benzotriazole (metal corrosion inhibitor), methylisothiazolinone (fungicide), and butylated hydroxytoluene (antioxidant). The ester base oil is neopentyl glycol dioleate. The environmentally friendly emulsifier is prepared by mixing environmentally friendly sodium petroleum sulfonate and fatty alcohol ether emulsifier in a mass ratio of 3:1.

[0104] A method for preparing an ester-based semi-synthetic cutting fluid comprises the following steps:

[0105] S21: Heat the ester base oil to 65°C; maintain the constant temperature for 30 minutes to ensure complete heating of the base oil and removal of impurities.

[0106] S22: Gradually add environmentally friendly emulsifier to the heated base oil, mix while stirring to ensure that the emulsifier is fully and evenly dispersed in the oil phase, and maintain a medium stirring speed to form a stable emulsified system; the stirring speed is controlled at 1000rpm, and stirring is continued for 20 minutes to form a stable emulsified system.

[0107] S23: Mix the vegetable oil and the phosphate ester uniformly according to the mass ratio to ensure that the two are fully mixed, and then separate them into reagent A and reagent B for later use;

[0108] S24: gradually adding nano zinc titanate to reagent A and preliminarily dispersing it by high shear stirring or ultrasonic treatment can ensure that the nanoparticles are distributed in the liquid as evenly as possible and reduce the possibility of initial agglomeration; then after the nanoparticles are preliminarily dispersed, slowly adding polyvinyl alcohol and continuing stirring for 30 minutes to effectively prevent the reagglomeration of the particles, and then slowly adding the obtained suspension to the heated emulsification system and continuing stirring to ensure that the nano additives are evenly dispersed;

[0109] S25: adding reagent B to the emulsified system mixed in step S24, and continuing to stir to ensure uniformity;

[0110] S26: Add low-carbon additives as needed and stir to mix evenly, keep stirring at a low speed to cool to prevent stratification or precipitation, and obtain an ester-based semi-synthetic cutting fluid after cooling.

[0111] Performance Testing

[0112] Antibacterial performance: Referring to GB15981-1995, Q / 02GZS001 detection methods and standards, after 72 hours of antibacterial test, the inhibitory effect of cutting fluid on common bacteria (Escherichia coli, Staphylococcus aureus) was tested.

[0113] Hydrolysis resistance: After testing for 72 hours at 50°C and 90% relative humidity, the degree of hydrolysis of the ester base oil is evaluated by the increase in acid value.

[0114] Antioxidant performance: The antioxidant performance of each group of samples of equal quality was measured according to the ASTM D2272 test method.

[0115] Four-ball test: The relevant performance of each group of samples of equal quality is measured according to the GB / T3142 test method.

[0116]

[0117] As shown above, in Examples 1 to 3, the cutting fluid has excellent antibacterial properties and can inhibit the reproduction of bacteria in the liquid. The composite self-repairing lubricant not only effectively inhibits the hydrolysis reaction of the ester base oil, but also extends the service life of the cutting fluid. Phosphate esters also have certain antioxidant properties. The phosphate group forms a protective film on the metal surface, reducing the reaction of oxygen, nitrogen, etc. with the metal surface at high temperatures to generate titanium oxide. In the cutting of high-temperature titanium alloys, it avoids work hardening and tool passivation caused by oxidation, while protecting the surface quality of the workpiece and extending the service life of the cutting tool. The four-ball test shows that the cutting fluid has excellent lubrication and wear resistance under high temperature and high pressure conditions, and is very suitable for the high-intensity cutting requirements of difficult-to-process materials such as titanium alloys.

[0118] In Comparative Example 1, the self-repairing lubricant is not divided into two parts, and polyvinyl alcohol is not added. The nano-additive is directly added to the emulsified system, and the dispersion effect of the nano-additive is poor. This shows that the present invention divides the self-repairing lubricant into two parts, one part (reagent A) is mixed with the nano-additive (modified nano zinc titanate system), polyvinyl alcohol is added to form a suspension, and the other part (reagent B) is directly added to the cutting fluid system; polyvinyl alcohol has good dispersibility, which further prevents the agglomeration of nanoparticles; it achieves efficient dispersion of nanoparticles, improves the anti-wear performance of the cutting fluid, and increases the viscosity of the suspension by polyvinyl alcohol, thereby promoting the formation of a lubricating film and reducing friction and wear. This design optimizes the fluidity and stability of the cutting fluid.

[0119] In Comparative Example 2, no self-repairing lubricant was added, and polyvinyl alcohol was used to assist in dispersion. It can be seen that due to the lack of self-repairing lubricant, the hydrolysis resistance and oxidation resistance are relatively low, and the extreme pressure performance and friction coefficient are also relatively poor, indicating that a strong lubricating film is formed on the metal surface. When the lubricating film is partially damaged due to high temperature or mechanical stress on the metal surface, the unreacted molecules of the vegetable oil-based phosphate can migrate back to the damaged area, automatically adsorb and repair the worn area; this self-repairing mechanism ensures that the lubricating film maintains continuity and stability during the cutting process, effectively reduces the friction between the tool and the workpiece, extends the service life of the tool, reduces downtime for maintenance, and at the same time improves processing efficiency and precision, especially in the high-temperature cutting environment of titanium alloys.

[0120] In Comparative Example 3, the nano additive is unmodified zinc titanate particles, and it can be seen that all performances have declined. The main reason is that the unmodified nano zinc titanate has poor dispersibility and cannot effectively reduce friction, which reduces its anti-wear effect in the cutting fluid. It can be seen that the modified nano zinc titanate system in the present invention can maintain good dispersibility and stability in the cutting fluid due to its high hardness and low surface energy after modification by titanate coupling agent, and continuously provide lubrication and anti-wear protection; this combination enhances the anti-wear ability of the cutting fluid in the processing of high-strength materials such as titanium alloys, effectively reduces tool wear during high-temperature cutting, extends the tool life, and improves the overall stability of the cutting process.

[0121] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. An ester-based semi-synthetic cutting fluid, characterized in that: According to the mass percentage, including 50~70 parts of ester base oil; 10~20 parts of environmentally friendly emulsifier; 5~10 parts of nano additives; 5~10 parts of self-repairing lubricant; 1~5 parts of low carbon additives; Polyvinyl alcohol 0.5~1 part; The self-repairing lubricant is divided into reagent A and reagent B in a ratio of 5-7:3-5, the reagent A is mixed with the nano additive and added to the polyvinyl alcohol to form a suspension and then added to the reaction system; the reagent B is used to be directly added to the reaction system; the self-repairing lubricant is a vegetable oil composite phosphate, the mass ratio of the phosphate to the vegetable oil is 3-6:5-10; the vegetable oil is one or more of coconut oil and rapeseed oil, and the phosphate is triethyl phosphate or diethyl phosphate; The nano additive is nano zinc titanate modified by a titanate coupling agent, and the particle size of the nano zinc titanate modified by a titanate coupling agent is in the range of 10 to 50 nm.

2. An ester-based semi-synthetic cutting fluid according to claim 1, characterized in that: The ester base oil includes one or more of neopentyl glycol dioleate, triethylene glycol dioleate, pentaerythritol oleate, pentaerythritol tetraisooctanoate, and dipentaerythritol oleate.

3. An ester-based semi-synthetic cutting fluid according to claim 1, characterized in that: The environmentally friendly emulsifier includes environmentally friendly sodium petroleum sulfonate and fatty alcohol ether emulsifier, and the environmentally friendly sodium petroleum sulfonate and fatty alcohol ether emulsifier are mixed in a mass ratio of 3:

1.

4. An ester-based semi-synthetic cutting fluid according to claim 1, characterized in that: The nano additive is prepared by the following steps: S11: Add nano zinc titanate to ethanol solvent, ultrasonically vibrate evenly, slowly add titanate coupling agent, and keep stirring to ensure uniform mixing; S12: using ultrasonic oscillation and mechanical stirring to allow the titanate coupling agent to coat the surface of the nano zinc titanate to form a modified film; S13: After the reaction is completed, the unreacted reactants and impurities are removed by centrifugation or filtration, and the washed product is dried in a vacuum environment at 60-80° C. to remove the residual solvent, thereby obtaining a surface-modified nano-additive.

5. The ester-based semi-synthetic cutting fluid according to claim 1, characterized in that: The low-carbon additives include one or more of metal corrosion inhibitors, bactericides, and antioxidants.

6. The ester-based semi-synthetic cutting fluid according to any one of claims 1 to 5, characterized in that: The preparation method of the ester-based semi-synthetic cutting fluid comprises the following steps: S21: Heat the ester base oil to 60-70°C; S22: gradually add environmentally friendly emulsifier to the heated base oil, stirring and mixing to ensure that the emulsifier is fully and evenly dispersed in the oil phase, and keep the stirring speed at a medium speed to form a stable emulsified system; S23: Mix the vegetable oil and the phosphate ester uniformly according to the mass ratio to ensure that the two are fully mixed, and then separate them into reagent A and reagent B for later use; S24: gradually adding the nano-additive to reagent A and preliminarily dispersing it by high shear stirring or ultrasonic treatment, then adding polyvinyl alcohol and continuing stirring for 30 minutes to ensure that the nano-particles are evenly dispersed and to avoid particle agglomeration, then slowly adding the obtained suspension to the heated emulsification system and continuing stirring to ensure that the nano-additive is evenly dispersed; S25: adding reagent B to the emulsified system mixed in step S24, and continuing to stir to ensure uniformity; S26: Add low-carbon additives as needed and stir to mix evenly, and obtain the ester-based semi-synthetic cutting fluid after cooling.

7. An ester-based semi-synthetic cutting fluid according to claim 6, characterized in that: In step S26, low-speed stirring is maintained during the cooling process to prevent stratification or precipitation.

Citation Information

Patent Citations

  • Environment-friendly semisynthetic cutting fluid for titanium alloys as well as preparation method and application of cutting fluid

    CN105176656A

  • Preparation method of cutting fluid capable of improving corrosion resistance of magnesium alloy

    CN107325861A

  • Lubricating oil with self-repairing function and preparation method thereof

    CN111057607A